Multidisciplinary information retrieval : 5th International retrieval facility conference, IRFC 2012, Vienna, Austria, July 2-3, 2012 Proceedings - Larsen, Birger; Salampasis, Michail (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of the 5th International Information Retrieval Facility Conference, IRFC 2012, held in Vienna, Austria, July 2-3, 2012. The 12 papers presented were carefully reviewed and selected from 17 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. This fifth conference aimed to tackle four complementary research areas: information retrieval, machine translations for search solutions, and interactive information access. The papers are organized into topical sections on patent search, Web search, applications, and query formulation and analysis.